2009
DOI: 10.1111/j.1365-2133.2008.08952.x
|View full text |Cite
|
Sign up to set email alerts
|

Some epidermolysis bullosa acquisita sera react with epitopes within the triple-helical collagenous domain as indicated by immunoelectron microscopy

Abstract: Our results suggest that epitopes within the T-H collagenous domain of type VII collagen are recognized by IgG antibodies from some EBA sera. These antibodies appear to be found in patients with inflammatory-type EBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 10 publications
1
21
1
1
Order By: Relevance
“…However, in our cohort of 69 EBA patients, we found no correlation of clinical phenotype with the fine specificity of anti-COL7 IgG. We do not think that reactivity to the collagenous domain of COL7 can explain these findings, as only very few patients had been described to have reactivity to epitopes located within the collagenous domain and/or the hinge region of COL7 (Ishii et al, 2009). Hence, other factors are likely to cause the different clinical phenotypes.…”
Section: Discussioncontrasting
confidence: 75%
“…However, in our cohort of 69 EBA patients, we found no correlation of clinical phenotype with the fine specificity of anti-COL7 IgG. We do not think that reactivity to the collagenous domain of COL7 can explain these findings, as only very few patients had been described to have reactivity to epitopes located within the collagenous domain and/or the hinge region of COL7 (Ishii et al, 2009). Hence, other factors are likely to cause the different clinical phenotypes.…”
Section: Discussioncontrasting
confidence: 75%
“…It has been reported that autoantibodies in some EBA patients bind only to the central collagenous domain of type VII collagen [14]. The serum of this case may bind to the central collagenous domain of type VII collagen.…”
Section: Discussionmentioning
confidence: 96%
“…NC2 domain of type VII collagen contains minor antigenic epitopes [11,12]. Moreover, some EBA cases bind to the central collagenous domain of type VII collagen [13][14][15].…”
mentioning
confidence: 99%
“…Detailed epitope mapping studies with sera from EBA patients [5557] demonstrated that most autoantibodies bind to epitopes located within the noncollagenous (NC) 1 domain of COL7 (Figure 2). In only very few patients, antibody reactivity to either the collagenous domain [58] or the NC2 domain [59] can be detected.…”
Section: Identification Of Type VII Collagen As the Autoantigen Inmentioning
confidence: 99%